Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/jfpp.12732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Properties of Symbiotic Yoghurt of Buffalo Milk

Abstract: In present study the set-type yoghurt samples were prepared from buffalo milk, Lactobacillus acidophilus and Bifidobacterium bifidium as probiotics and lactoluse, oligofructose and inulin as prebiotics. Changes in pH value, syneresis and probiotic counts along with sensorial properties were tested in all of yoghurt samples after preparation up to 21 days at 4C. According to the results of pH test, post acidification with a range of 4.53-3.93 was observed. Using prebiotics simultaneously led to the significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
4
19
0
Order By: Relevance
“…in synbiotic yogurt increased in enhanced samples with 1 and 2% ulvan polysaccharide; which confirmed the synergistic effect between these bacteria due to their mutual interactions and the addition of ulvan polysaccharide as a prebiotic. These results are compatible with that demonstrated before by Gustaw et al [33] and Ehsani et al [34] who confirmed that the incorporation of inulin, oligofructose, and other types of fibers as prebiotics improved the growth of, Bifidobacterium sp. and Lactobacillus acidophilus probiotic bacteria.…”
Section: Firmnesssupporting
confidence: 93%
See 4 more Smart Citations
“…in synbiotic yogurt increased in enhanced samples with 1 and 2% ulvan polysaccharide; which confirmed the synergistic effect between these bacteria due to their mutual interactions and the addition of ulvan polysaccharide as a prebiotic. These results are compatible with that demonstrated before by Gustaw et al [33] and Ehsani et al [34] who confirmed that the incorporation of inulin, oligofructose, and other types of fibers as prebiotics improved the growth of, Bifidobacterium sp. and Lactobacillus acidophilus probiotic bacteria.…”
Section: Firmnesssupporting
confidence: 93%
“…The further decreasing of pH during post-acidification caused these reductions in the viability of probiotic bacteria in synbiotic yogurt; also, Bifidobacterium was more susceptible to aerobic conditions during the cold storage. These findings are consonant with that observed by Eskandari et al [28] Gustaw et al [33], and Ehsani et al [34].…”
Section: Firmnesssupporting
confidence: 93%
See 3 more Smart Citations